Artistic and creative therapies in improving psychological distress in women with breast cancer. Systematic review - Rabadán, Jennifer; Chamarro, Andrés; Álvarez, María (Psicooncología, 2017)
Objective: To know the current state of the effectiveness of artistic and creative therapies (ACTs) over psychological distress of women with breast cancer and to delimit it according to the type of CT and the therapeutic moment of the patient. Method: The search was performed using Pubmed, Web of Science, Psychinfo and Google Academic databases for the period 2010-2016. Results: nine controlled RTC and quasi-experimental studies (2 of Dance movement therapy, 1 of Art Therapy, 1 of Music therapy and 5 of Musical Listening) were obtained, including 680 participants. Methodological quality, risk of bias and measures of therapeutic efficacy are discussed. Conclusions: ACT scans seem to be short-term complementary aid during the treatment phase in breast cancer. However, more trials are needed to clarify the mechanisms underlying the improvement as well as to delimit the effectiveness of each modality.
Keywords: Breast cancer; creative therapy; artistic therapy; music therapy; dance movement therapy; art therapy.